A STUDY ON FUNCTIONAL OUTCOME OF ANTERIOR VERSUS POSTERIOR CIRCULATION STROKE TREATED WITH INTRAVENOUS THROMBOLYSIS - SANJAYKUMAR KAMINWAR; TEJASWI G; THIMMINENI HARITHA; YENNAM NARESH; SHANMUGARAJU P (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: In this study, the objective was to evaluate the functional outcome of intravenous thrombolysis in anterior versus posterior circulation stroke (PCS) patients. Methods: A total of 41 patients were enrolled during the study. This study was conducted at the Department of Neurology, Chalmeda Anand Rao Institute of Medical Sciences, Karimnagar. The modified Rankin Scale score was used assessed outcome and at the 3-month follow-up in patients with intracerebral hemorrhage stroke. Results: In this study, 73% in anterior circulation stroke (ACS) and 81% in PCS. Mean NIHSS score is 10.7 in ACS and 8.6 in PCS with a significant difference (p<0.008) between two groups. Conclusion: Our study shows that patients with PCS had significantly lower baseline NIHSS scores (8.6%) as compared with those with ACS (10.7%) in the present study which is statistically significant. NIHSS score at 24 h is 5.8% for ACS and 3.8% for PCS.